19F NMR as a Probe of Ligand Interactions with the iNOS Binding site of SPRY Domain‐Containing SOCS Box Protein 2. (5th June 2014) - Leung, Eleanor W. W.; Yagi, Hiromasa; Harjani, Jitendra R.; Mulcair, Mark D.; Scanlon, Martin J.; Baell, Jonathan B.; Norton, Raymond S.
<x xml:space="preserve">Abstract</x> SPRY domain‐containing SOCS box protein 2 (SPSB2) regulates inducible nitric oxide synthase (iNOS) by targeting it for proteasomal degradation. Inhibiting this interaction prolongs the intracellular lifetime of iNOS, leading in turn to enhanced killing of infectious pathogens such as bacteria and parasites. SPSB2 recognizes a linear motif (DINNN) in the disordered N‐terminus of iNOS, and ligands that target the DINNN binding site on SPSB2 are potentially novel anti‐infective agents. We have explored 19F NMR as a means of probing ligand binding to SPSB2. All six Trp residues in SPSB2 were replaced with 5‐fluorotryptophan (5‐F‐Trp) by utilizing a Trp auxotroph strain of Escherichia coli. The labeled protein was well folded and bound a DINNN‐containing peptide with similar affinity to native SPSB2. Six well‐resolved 5‐F‐Trp resonances were observed in the 19F NMR spectrum and were assigned using site‐directed mutagenesis. The 19F resonance of W207 was significantly perturbed upon binding to DINNN‐containing peptides. Other resonances were perturbed to a lesser extent although in a way that was sensitive to the composition of the peptide. Analogues of compounds identified in a fragment screen also perturbed the W207 resonance, confirming their binding to the iNOS peptide‐binding site on SPSB2. 19F NMR promises to be a valuable approach in developing inhibitors that bind to the DINNN binding site.